Implikasi Perbedaan Klasifikasi AWaRe WHO Dan Kemenkes RI Terhadap Evaluasi Penggunaan Antibiotik: Tinjauan Literatur - Yusna Fadliyyah Apriyanti; Reza Rahmawati; Muthia Nurhidayah; Baha Udin (Jurnal Pharmacopoeia, 2026)
The WHO developed the AWaRe classification to support antimicrobial stewardship through standardized evaluation of antibiotic use. Several countries, including Indonesia, have implemented AWaRe classifications tailored to national clinical needs and policy priorities. However, these adaptations may lead to variations in the interpretation of antibiotic use indicators and stewardship performance. A literature search was conducted through the PubMed and ScienceDirect databases and other relevant databases with the keywords “AWaRe classification”, “antibiotic use evaluation”, “WHO”, and “Indonesia”, combined with the Boolean operators “AND” and “OR" and selection by the publication date starting January 2023 and ten (10) studies met the inclusion criteria. The selected studies were analyzed using thematic and comparative synthesis to identify patterns of antibiotic consumption, dominance of AWaRe categories, and the impact of classification differences on stewardship indicators. The included studies covered outpatient care (30%), inpatient care (30%), intensive care units (20%), community pharmacies (10%), and national antibiotic distribution (10%). Most studies (90%) reported dominance of Watch antibiotics, while increased use of Reserve antibiotics (40%) and Watch antibiotics dominated the DU90% segment (80%) of studies. Indonesian studies (20%) showed that national adaptation of the AWaRe classification increased the proportion of Access antibiotics by approximately 15–30%.  In conclusion, AWaRe is a valuable tool for monitoring antibiotic use; however, stewardship interpretation is sensitive to the classification system applied. Dual reporting using both WHO and Kemenkes RI AWaRe classifications is recommended to ensure accurate, transparent, and globally comparable evaluation of antibiotic use in support of effective antimicrobial stewardship policies.